Between support and marginalization: The process of the Diaguita’s re-emergence in the age of neoliberal multiculturalism (Chile) - Gajardo, Anahy (Abya-yala: Revista sobre Acesso à Justiça e Direitos nas Américas, 2018)
Long regarded as an ethnic group extinct since the 16th century, the Diaguita of Chile re-emerged as an indigenous people in the early 2000s in the midst of their struggle against extractivism. Although they did not „exist”Ÿ 15 years ago in legal terms and were socially invisible, they are now the third most important indigenous group in Chile, after the Mapuche and the Aymara. This paper analyses the combined roles of a Canadian mining company (Barrick Gold, Pascua Lama project) and the Chilean state in the process of this group”Ÿs re-emergence in the Huasco Alto region of northern Chile. In particular, it shows how the social responsibility programs of the mining company (CSR), set up to support “the ethnic revitalization” of the Diaguita, contribute both to divide local indigenous communities and to justify a culturalized and depoliticized indigenous identity, compatible with mining interests and the state's project to conciliate neoliberal and multiculturalist policies.